2023
DOI: 10.1101/2023.10.20.563154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivoaffinity maturation of murine B cells reprogrammed to express human antibodies

Yiming Yin,
Yan Guo,
Yuxuan Jiang
et al.

Abstract: CRISPR-edited murine B cells engineered to express human antibody variable chains proliferate, class switch, and secrete these antibodies in vaccinated mice. However, current strategies disrupt the heavy-chain locus, resulting in inefficient somatic hypermutation without functional affinity maturation. Here we show that recombined murine heavy- and kappa-variable genes can be directly and simultaneously overwritten, using Cas12a-mediated cuts at their 3'-most J segments and 5' homology arms complementary to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…We have recently shown that when heavy- and light-chain sequences of HIV-1 and SARS-CoV-2 neutralizing antibodies were introduced at the V(D)J-recombined regions of their respective mouse loci, the resulting BCR affinity matured after immunization 18, 32 . However, many protein-based therapeutics are not antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that when heavy- and light-chain sequences of HIV-1 and SARS-CoV-2 neutralizing antibodies were introduced at the V(D)J-recombined regions of their respective mouse loci, the resulting BCR affinity matured after immunization 18, 32 . However, many protein-based therapeutics are not antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…1c and d). This efficiency is higher than necessary for expansion and affinity maturation of engineered B cells 16,18,32 . Thus, primary murine B cells can be engineered ex vivo to efficiently express D1D2-OKT3-V H .…”
Section: Engineering Primary Mouse B Cells To Express a Protein Biolo...mentioning
confidence: 94%
See 1 more Smart Citation
“…We have shown that introduction of human antibody heavy chain complementarity determining regions (HCDR3s) or heavy-and light-chain variable genes into their respective murine loci enabled in vivo affinity maturation of the resulting chimeric BCRs 18,32 . Extension of this approach to immunoadhesins such as CD4-Ig is complicated by the absence of the first heavy constant region 1 (CH1) that noncovalently associates with a light-chain constant domain.…”
Section: Engineering Primary Mouse B Cells To Express a Protein Biolo...mentioning
confidence: 99%
“…1b). Accordingly, we introduced a double-stranded break by CRISPR/Mb2Cas12a ribonucleoproteins (RNPs) into the 3'-most JH segment, JH4 in mice 18,32,33 . Repair of this break was guided by a homology-directed repair template (HDRT) delivered by recombinant adeno-associated virus DJ (AAV-DJ).…”
Section: Engineering Primary Mouse B Cells To Express a Protein Biolo...mentioning
confidence: 99%